On the stable coexistence of the orthorhombic and rhombohedral symmetries in BiFeO3 compound. (11th June 2019) - Astrath, E. A. C.; Junior, L. S.; Silva, D. M.; Dias, G. S.; Volnistem, E. A.; Bini, R. D.; Oliveira, R. C.; Bonadio, T. G. M.; Santos, I. A.; Cótica, L. F.; Freitas, V. F.
Abstract: BiFeO3 nanoparticles (<200 nm) were synthesized using the Pechini method and submitted to structural, microstructural, magnetic and electrical investigations. Two different structural symmetries were proposed to describe the BiFeO3 structure and the observed electrical properties, rhombohedral ( R 3 c space group) and orthorhombic ( Pbmn ). Electric conductivity results obtained as a function of temperature, show two completely reversible changes in the baseline (310 °C and 385 °C), indicating two magnetic corresponding transitions associated with the orthorhombic and rhombohedral symmetries. These transitions were linked to predicted insulating-metal transition when magnetic arrangement changes from antiferromagnetic to a nonmagnetic ordering.